Stimulation of Vibratory Urticaria-Associated Adhesion-GPCR, EMR2/ADGRE2, Triggers the NLRP3 Inflammasome Activation Signal in Human Monocytes - I, Kuan-Yu; Tseng, Wen-Yi; Wang, Wen-Chih; Gordon, Siamon; Ng, Kwai-Fong; Lin, Hsi-Hsien (Frontiers in Immunology, 2021)
EMR2/ADGRE2 is an adhesion G protein-coupled receptor differentially expressed by human myeloid cells. It modulates diverse cellular functions of innate immune cells and a missense EMR2 variant is directly responsible for vibratory urticaria. Recently, EMR2 was found to activate NLRP3 inflammasome in monocytes via interaction with FHR1, a regulatory protein of complement Factor H. However, the functional involvement of EMR2 activation and its signaling mechanisms in eliciting NLRP3 inflammasome activation remain elusive. In this study, we show that EMR2-mediated signaling plays a critical role in triggering the activation (2nd) signal for the NLRP3 inflammasome in both THP-1 monocytic cell line and primary monocytes. Stimulation of EMR2 by its agonistic 2A1 monoclonal antibody elicits a Gα16-dependent PLC-β activation pathway, inducing the activity of downstream Akt, MAPK, NF-κB, and Ca2+ mobilization, eventually leading to K+ efflux. These results identify EMR2 and its associated signaling intermediates as potential intervention targets of NLRP3 inflammasome activation in inflammatory disorders.